Transcriptomic analyses provide new insights into green and purple color pigmentation in Rheum tanguticum medicinal plants - Haixia Chen; Tsan-Yu Chiu; Sunil Kumar Sahu; Haixi Sun; Jiawen Wen; Jianbo Sun; Qiyuan Li; Yangfan Tang; Hong Jin; Huan Liu (PeerJ, 2022)
Background Rheum tanguticum Maxim. ex Balf is a traditional Chinese medicinal plant that is commonly used to treat many ailments. It belongs to the Polygonacae family and grows in northwest and southwest China. At high elevations, the color of the plant’s young leaves is purple, which gradually changes to green during the growth cycle. Anthraquinone, which is known for various biological activities, is the main bioactive compound in R. tanguticum. Although a significant amount of research has been done on R. tanguticum in the past, the lack of transcriptome data limits our knowledge of the gene regulatory networks involved in pigmentation and in the metabolism of bioactive compounds in Rheum species. Methods To fill this knowledge gap, we generated high-quality RNA-seq data and performed multi-tissue transcriptomic analyses of R. tanguticum. Results We found that three chlorophyll degradation enzymes (RtPPH, RtPao and RtRCCR) were highly expressed in purple samples, which suggests that the purple pigmentation is mainly due to the effects of chlorophyll degradation. Overall, these data may aid in drafting the transcriptional network in the regulation and biosynthesis of medicinally active compounds in the future.